The Informational Content of Implied Volatility - Canina, Linda; Figlewski, Stephen (Review of Financial Studies, 1993)
[Implied volatility is widely believed to be informationally superior to historical volatility, because it is the "market's" forecast of future volatility. But for S&P 100 index options, the most actively traded contract in the United States, we find implied volatility to be a poor forecast of subsequent realized volatility. In aggregate and across subsamples separated by maturity and strike price, implied volatility has virtually no correlation with future volatility, and it does not incorporate the information contained in recent observed volatility.]